Silver Sulphadiazine- xanthan gum- hyaluronic Acid Composite Hydrogel for Wound Healing: Formulation Development and in vivo Evaluation (Nigerian Journal of Pharmaceutical Research, 2020)
Background: Development and modifications of hybrid hydrogels have been done to improve biological properties or to decrease the disadvantages of biomaterials. Objectives: The efficacy of hyaluronic acid in combination with silver sulphadiazine in wound healing was investigated. The retaining properties of xanthan gum to aid re- epithelialization was also explored. Materials and Method: Four hybrid hydrogels comprising of different concentrations of xanthan gum, eugenol and antimicrobial agents – hyaluronic acid and silver sulphadiazine were formulated. The physicochemical properties of the gels were assessed, and the antimicrobial effectiveness of the different hydrogel were determined using the extent of wound closure as an index.Results: The hydrogel samples had approximately 90% moisture content with rate of evaporation between 26- 32% for a 5 h period at 37oC. The pH of all formulations was between 7.59 - 8.05 considering that the formulation would be applied to underlying tissues of the skin. The swelling index after a 12 h period in distilled water was 10% for HX 1, 27% for HX 2, 29% for HX 3 and 30% for HX 4. There was no new peak observed in the FTIR analysis to indicate formation of new bonds.Conclusion: Incorporation of silver sulphadiazine at 0.1% and hyaluronic acid at 1.5% in the formulation yielded the best results with regards to least presence of inflammatory cell infiltrates and excellent wound closure at 14 days compared to the control and other formulations. Further investigation may be required for clinical use as an effective wound dressing material.
Keywords: Silver sulphadiazine; Xanthan gum; Hyaluronic acid; Hydrogels; Wound healing